EDUKASI PERILAKU BERINTEGRITAS PADA SANTRI PONDOK PESANTREN DARUTTAUBAH - Bangun, Mic Finanto Ario; Syauket, Amalia (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Integrity means strength, wholeness, completeness, and invulnerability. Integrity behaviour refers to the unity of self and moral honesty. Integrity shows consistency between words and actions in daily life. A person with integrity usually thinks before speaking so that their behaviour and actions align with what is said. Santri is a term for someone who learns or seeks Islamic religious knowledge at a pesantren (Islamic boarding school) in Indonesia. Santri usually lives at the pesantren to follow an educational process involving the teaching of spiritual knowledge. The community service program with the theme "Towards Golden Indonesia 2045 with the Spirit of Santri Based on Intellectuality, Integrity, and Anti-Bullying in the Digital Era," conducted for the santri at Pondok Pesantren Daarut Taubah, aims to increase the awareness of santri to avoid behaviours that lack integrity in the school, family, and community environments, and to make santri individuals who are of integrity, dedicated, and useful to society.